Work Happy, Perform Better: The Unseen Connection Between Satisfaction, Commitment, and Success in Public Service - Sihombing, Maryto Maretis; Manafe, Leonard Adrie; Chamid, Abdul (LPPPIPublishing, 2025)
This study investigates the relationship between job satisfaction, employee commitment, and employee performance at the Surabaya City Statistics Agency (BPS). The researchers applied a qualitative case study methodology, utilising in-depth interviews, field observations, and analysis of official documents to gather data holistically. As information sources, six employees from various units were selected through purposive sampling to ensure that the perspectives obtained covered a diverse spectrum of work. Empirical findings indicate that high job satisfaction built by a friendly work environment and a reward system considered fair directly contributes positively to employees' daily performance. In addition, employee attachment to the institution, particularly the dimension of affective commitment, was also found to encourage better performance. However, this study also noted several obstacles, such as a relatively heavy workload and limited opportunities for career development. Therefore, the researchers recommend that the Surabaya City Statistics Agency formulate balanced policies to optimise employee satisfaction, commitment, and productivity simultaneously. As a result, the findings of this study are not only practical but also enrich theoretical research on human resource management in the public sector.